Diffusion tensor imaging suggests extrapontine extension of pediatric diffuse intrinsic pontine gliomas. Issue 4 (April 2016) - Wagner, Matthias W.; Bell, W. Robert; Kern, Jason; Bosemani, Thangamadhan; Mhlanga, Joyce; Carson, Kathryn A.; Cohen, Kenneth J.; Raabe, Eric H.; Rodriguez, Fausto; Huisman, Thierry A.G.M.; Poretti, Andrea
Highlights: Quantitative DTI analysis suggests extrapontine extension of DIPG tumor cells. Lower FA/AD and higher RD values in the PLIC characterize early tumor extension. Changes in DTI scalars between DIPG and LGBG argue against Wallerian degeneration. Abstract: Purpose: To apply DTI to detect early extrapontine extension of pediatric diffuse intrinsic pontine glioma along the corticospinal tracts. Methods: In children with diffuse intrinsic pontine glioma, low-grade brainstem glioma, and age-matched controls, DTI metrics were measured in the posterior limb of the internal capsule and posterior centrum semiovale. Histological examination was available in one patient. Results: 6 diffuse intrinsic pontine glioma, 8 low-grade brainstem glioma, and two groups of 25 controls were included. In diffuse intrinsic pontine glioma compared to controls, fractional anisotropy was lower in the bilateral posterior limb of the internal capsule, axial diffusivity was lower in the bilateral posterior centrum semiovale and posterior limb of the internal capsule, while radial diffusivity was higher in the bilateral posterior limb of the internal capsule. No significant differences were found between low-grade brainstem glioma and controls. In diffuse intrinsic pontine glioma compared to low-grade brainstem glioma, axial diffusivity was lower in the bilateral posterior limb of the internal capsule. Histological examination in one child showed tumor cells in the posterior limb of the internal capsule. Conclusion: Reduction in fractional anisotropy and axial diffusivity and increase in radial diffusivity in diffuse intrinsic pontine glioma may reflect tumor extension along the corticospinal tracts as shown by histology. DTI may detect early extrapontine tumor extension in diffuse intrinsic pontine glioma before it becomes apparent on conventional MRI sequences.